Peran Media Audio Visual Untuk Meningkatkan Kualitas Belajar Siswa Mata Pembelajaran Pendidikan Agama Islam - Zahra Novitasari, Nihaya; Zuhdi, Ahmad; Fatiatun (Universitas Majalengka, 2023)
The aim of this research is to determine the role of audio-visual media in improving the quality of learning for students studying Islamic Religious Education class VIII at Takhassus Al-Qur'an Middle School, Kalibeber. This research uses a qualitative method with a descriptive qualitative type. In this research, the techniques used for collecting data were observation, interviews and documentation. The subjects of the research used were class VIII Islamic Religious Education teachers and class VIII students at Takhassus Al-Qur'an Kalibeber Middle School. The results of the research show that the use of audio-visual media is very capable of improving the quality of student learning in Islamic Religious Education learning. During the learning process, students showed quite high interest in learning, then students were very enthusiastic about learning using audio-visual media. Based on the results of this research, it can be concluded that the use of audio-visual media to improve the quality of student learning in Islamic Religious Education is quite effective, both in terms of attracting students' attention and increasing satisfactory learning outcomes.